Analisis Keterampilan Membaca Siswa Kelas VII di SMP IT Robbani Indralaya - Aisyah Ariesca Putri; Zakia Rahmadania; Nabilla Khairunnisa. S; Ririn Ayu Anjar Wani; Silvia Silvia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Reading ability is a fundamental skill that plays a crucial role in education, as it significantly contributes to students’ academic achievement and intellectual development. This study aims to analyze the reading skills of seventh-grade students at SMP IT Robbani Indralaya, focusing on both mechanical and comprehension aspects. The research employed a descriptive quantitative method by distributing questionnaires to 19 student respondents. The questionnaire instrument was designed based on two main aspects: mechanical skills (letter recognition, linguistic elements, and slow reading speed) and comprehension skills (understanding text meaning, evaluating content, and flexible reading speed). The analysis results showed that the majority of students were in the “Good” category (63.16%), while the rest were in the “Fair” category (36.84%). There were no students in the “Very Good” or “Poor” categories. Internal factors such as motivation and reading interest, as well as external factors such as family support and school facilities, were found to influence students' reading skills. This study recommends the implementation of continuous and collaborative literacy development efforts involving students, teachers, schools, and families to improve reading skills comprehensively.